2016
DOI: 10.3390/inorganics4020013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Applications in Catalysis of Polyoxometalate/Zeolite Composites

Abstract: An overview of the synthesis, characterization and catalytic applications of polyoxometalates/zeolites composites is given. The solids obtained by direct synthesis of the polyoxometalate in the presence of the zeolite are first described with their applications in catalysis. Those obtained by a direct mixing of the two components are then reviewed. In all cases, special care is taken in the localization of the polyoxometalate, inside the zeolite crystal, in mesopores or at the external surface of the crystals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Recently, we found that carbon-supported H 3 PW 12 O 40 could be used as a catalyst in the conversion of D,L-lactic acid to enantioselective blends of PLA [16]. Keggin heteropolyacid (HPA) is an important class of solid acids among which 12-tungstophosphoric acid (H 3 PW 12 O 40 , H 3 PW) is particularly important because it can be used in acid catalysis for greener processes [17, 18, 19, 20, 21]. It has been shown that the H 3 PW/C catalyst is an alternative for use in such reactions involving an inexpensive monomer of D,L-lactic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found that carbon-supported H 3 PW 12 O 40 could be used as a catalyst in the conversion of D,L-lactic acid to enantioselective blends of PLA [16]. Keggin heteropolyacid (HPA) is an important class of solid acids among which 12-tungstophosphoric acid (H 3 PW 12 O 40 , H 3 PW) is particularly important because it can be used in acid catalysis for greener processes [17, 18, 19, 20, 21]. It has been shown that the H 3 PW/C catalyst is an alternative for use in such reactions involving an inexpensive monomer of D,L-lactic acid.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Due to their high solubility, low surface area, and instability under reaction conditions, the processability of POMs alone is often poor. 5 To overcome these undesirable properties, significant efforts have been made to heterogenize POMs on a variety of supports, including mesoporous silica, 27,28 high surface area carbon, 29,30 zeolites, 31 polymers, 32 metal−organic macrocycles, 33 covalent−organic frameworks, 34 and metal−organic frameworks (MOFs), among others. 35 Unlike conventional supports, MOFs offer a highly tunable, crystalline scaffold for anchoring small to large molecules.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Polyoxometalates (POMs) as soluble anionic metal oxide clusters of d-block transition metals in high oxidation states, typically W(VI), Mo(V,VI) or V(IV,V), exhibit redox and acid-base properties and are particularly exploited in catalysis, either in homogeneous conditions 1,2 or immobilized in solid supports. [3][4][5][6] In the hot field of solar energy conversion, although numerous studies have revealed their potentialities as catalysts for water splitting, [7][8][9][10] there have been scarce reports on POMs for CO2RR. 11,12 Besides rare examples of transition metal (M)-substituted polyoxotungstates, [13][14][15][16] reduced polyoxomolybdates (i.e.…”
Section: Introductionmentioning
confidence: 99%